2002
DOI: 10.1074/jbc.m112456200
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Kinase c-Src Constitutes a Bridge between Cystic Fibrosis Transmembrane Regulator Channel Failure and MUC1 Overexpression in Cystic Fibrosis

Abstract: Cystic fibrosis (CF), a disease caused by mutations in the cystic fibrosis transmembrane regulator (CFTR) chloride channel, is associated in the respiratory system with the accumulation of mucus and impaired lung function. The role of the CFTR channel in the regulation of the intracellular pathways that determine the overexpression of mucin genes is unknown. Using differential display, we have observed the differential expression of several mRNAs that may correspond to putative CFTR-dependent genes. One of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
62
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(66 citation statements)
references
References 37 publications
4
62
0
Order By: Relevance
“…Having said this, the question arises -how might CFTR regulate MUC4 expression? Recent findings have clearly indicated that CFTR regulates the expression of several genes, including mucins (Tabary et al, 1999;Steagall et al, 2000;Gonzalez-Guerrico et al, 2002;Estell et al, 2003). CFTR regulates the MUC1 expression in CF-tracheobronchial epithelial cells via a mechanism that is mediated by c-src activation (Gonzalez-Guerrico et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Having said this, the question arises -how might CFTR regulate MUC4 expression? Recent findings have clearly indicated that CFTR regulates the expression of several genes, including mucins (Tabary et al, 1999;Steagall et al, 2000;Gonzalez-Guerrico et al, 2002;Estell et al, 2003). CFTR regulates the MUC1 expression in CF-tracheobronchial epithelial cells via a mechanism that is mediated by c-src activation (Gonzalez-Guerrico et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings have clearly indicated that CFTR regulates the expression of several genes, including mucins (Tabary et al, 1999;Steagall et al, 2000;Gonzalez-Guerrico et al, 2002;Estell et al, 2003). CFTR regulates the MUC1 expression in CF-tracheobronchial epithelial cells via a mechanism that is mediated by c-src activation (Gonzalez-Guerrico et al, 2002). Moreover, studies conducted in CFTR-knockout mice have demonstrated the aberrant mucus accumulation in the intestine (Thomsson et al, 2002), and MUC1 has been reported to be an important contributor to the CF intestinal phenotype (Hinojosa-Kurtzberg et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 72-amino-acid cytoplasmic domain of MUC1 (MUC1-CD) contains seven highly conserved tyrosine residues, four of which are confirmed phosphorylation sites and construct potential docking motifs for SH2 or SH3 domain -containing proteins, such as Src family kinases and growth factor receptor binding protein 2 (12,13). Thus far, epidermal growth factor receptor (14,15), PKCy (16), and Src (14,17,18) have been found to physically associate with and phosphorylate MUC1-CD. This indicates that MUC1, although without intrinsic kinase activity (19), could function as a scaffold protein in signal transduction.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in our hands, singlestranded DNA oligonucleotides have produced very consistent results supporting recent data from the laboratory of Yoon. 30,31 When correcting the tyrosinase gene in albino mouse melanocytes, ODNs produced pigmented cells, indicating gene repair in 60% of experiments, while RDOs produced pigmented cells in only 10%.…”
Section: Discussionmentioning
confidence: 99%